Cardiovascular Implications Of Metabolic Associated Fatty Liver Disease And Non-Alcoholic Fatty Liver Disease: An In-Depth Review - B S, Subhaja; Tullanithi, K M; Thulaseedharan, N. K (Journal of Neonatal Surgery, 2025)
Background: Both Non-Alcoholic Fatty Liver Disease (NAFLD) and Metabolic Associated Fatty Liver Disease (MAFLD) are becoming more well acknowledged as common liver disorders associated with substantial metabolic dysfunction. These conditions, which are marked by hepatic steatosis without binge drinking, are linked to an increased risk of cardiovascular diseases (CVD), an area that has not received enough attention. Objective: The objective of this study is to compile the most recent information on the cardiovascular effects of MAFLD and NAFLD, looking at their pathophysiological relationships, clinical outcomes, and possible treatment approaches. Methods: We carried out an extensive assessment of the literature, concentrating on the relationship between MAFLD/NAFLD and cardiovascular health, based on research that were published during the last ten years. The effects on cardiovascular risk factors, the processes relating hepatic steatosis to vascular pathology, and the impact of various liver illnesses on clinical outcomes, such as mortality and cardiovascular events, are important topics of research. Results: Through a number of processes, MAFLD and NAFLD are significantly linked to an elevated risk of cardiovascular disease. These comprise endothelial dysfunction, insulin resistance, dyslipidemia, and systemic inflammation. Increased risk of myocardial infarction, stroke, and heart failure, as well as accelerated atherosclerosis, have all been associated with the presence of hepatic steatosis. Furthermore, the metabolic syndrome that is frequently linked to chronic liver illnesses increases the risk of cardiovascular disease. Conclusion: Important factors that contribute to cardiovascular morbidity and death are MAFLD and NAFLD. The necessity for integrated management techniques that address the hepatic and cardiovascular elements of patient care is highlighted by their influence on cardiovascular health. Subsequent investigations have to concentrate on clarifying the exact processes that connect these liver disorders with cardiovascular pathology and assessing the effectiveness of focused therapies to reduce related hazards.